The governor's dilemma indirect governance beyond principals and agents - Abbott, Kenneth W.; Genschel, Philipp; Snidal, Duncan; Zangl, Bernhard 1967- (Oxford University Press, 2020)
Through twelve case studies, this book introduces a general theory of indirect governance based on the tradeoff between governor control and intermediary competence
Keywords: Gewalt; Indirektheit; Wirtschaft; Governance; Aufsatzsammlung